Test of Easy Factors and The Utilization of University Website in Supporting Student Learning Processes - Edy Prayitno; Deborah Kurniawati; Dini Fakta Sari; Muhammad Abdullah Alhusni (Journal of International Conference Proceedings (JICP), 2019)
The existence of a university website is an integral part of the existence of the university itself. But it is necessary to test the acceptance of the website for the user, how does the influence of the university website on student learning. The study was conducted using a quantitative descriptive approach with multiple linear regression analysis tools. Questionnaires were conducted on students as one of the website users by asking about the ease and usefulness of the website. Simultaneous test results on perceptions of benefits and perceptions of convenience show the results of Fcount in column F as much as 149,180, with a significance of 0,000, greater than the value of Ftable which is 0,139 with an error rate of 5% or in other words Fcount> Ftable (149,180> 0,139). Based on hypothesis testing criteria if Fcount> Ftable with a significance level of 0.000 Ftable (149,180> 0,139). Based on hypothesis testing criteria if Fcount> Ftable with a significance level of 0.000